2008
DOI: 10.2135/cropsci2007.08.0446
|View full text |Cite
|
Sign up to set email alerts
|

A Century of Clover Breeding Developments in the United States

Abstract: The perennial clovers, red (Trifolium pratense L.) and white clover (T. repens L.), have been important legumes for livestock feeding in the United States during the past century, particularly in the eastern United States. Recently, sustainable agriculture, organic farming, integrated crop–livestock systems, and high nitrogen prices have stimulated interest in forage legumes. This paper describes the present status of clover improvement programs—their objectives, successes, short falls, and challenges for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 82 publications
4
121
0
4
Order By: Relevance
“…are attractive to breeders and consumers alike due to their seedlessness and are usually derived from a tetraploid × diploid cross. In forage species like alfalfa (Medicago sativa L.) and red clover (Trifolium pratense L.), tetraploids are generally considered to have favourable agronomic characteristics and are widely employed (Taylor, 2008). Therefore, instead of retreating from the challenges of polyploidy, we could also embrace the developments in technology and bioinformatics which are helping to turn the key to open the polysomic "black box".…”
Section: Opening the Polysomic "Black Box"mentioning
confidence: 99%
See 1 more Smart Citation
“…are attractive to breeders and consumers alike due to their seedlessness and are usually derived from a tetraploid × diploid cross. In forage species like alfalfa (Medicago sativa L.) and red clover (Trifolium pratense L.), tetraploids are generally considered to have favourable agronomic characteristics and are widely employed (Taylor, 2008). Therefore, instead of retreating from the challenges of polyploidy, we could also embrace the developments in technology and bioinformatics which are helping to turn the key to open the polysomic "black box".…”
Section: Opening the Polysomic "Black Box"mentioning
confidence: 99%
“…Tetraploid clovers are often favoured over diploids due to their higher yields, greater persistence and higher levels of resistance to biotic and abiotic stresses (Taylor, 2008;Vleugels et al, 2016). However, the main drawback to tetraploid cultivars is their reduced seed yield (Vleugels et al, 2016).…”
Section: Where Next For Polysomic Polyploid Breeding?mentioning
confidence: 99%
“…However, in general isoflavones concentration is not a problem for large ruminants and little research has been conducted on breeding for lower isoflavones content in forage breeding programs in United States (Taylor, 2008). Contrary to large ruminants, high levels of isoflavones have been showed to cause infertility in ewes (Mcdonald, 1995;Moorby et al, 2004) and low phytoestrogens cultivars have been released in Australia and New Zealand (Oram, 1990;Rumball et al, 1997).…”
Section: Genetic Diversity For Isoflavones and Cluster Analysismentioning
confidence: 99%
“…Thus the high level of variation in total isoflavone concentration between cultivars could explain this partially structurxation related to improvement status. Moreover, the breeding schemes and the synthetic structure of the red clover cultivars with several parental families maintain a large within cultivar variation (Taylor, 2008). Papadopoulos et al (2006) showed in their study that total and individual isoflavone concentration in red clover plants presented a high genetic variability among thirteen red clover cultivars, and suggest that selecting individual plant phenotypes for high isoflavones contents would be highly effective for cultivars development.…”
Section: Genetic Diversity For Isoflavones and Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation